ANALISIS PENGARUH PENGAMBILAN KEPUTUSAN MAHASISWA BARU TERHADAP PEMILIHAN PROGAM STUDI MANAJEMAN UNIVERSITAS PGRI MADIUN TAHUN 2017 - Rizal Ula Ananta; Dian Citaningtyas Ari Kadi (CAPITAL: Jurnal Ekonomi dan Manajemen, 2017)
The background of this study aims to determine the influence of decision-making factors (Citra PT, Parents, peers and personality Individual / interest in the selection of university management program PGRI madiun 2017 This research uses survey method with questionnaire as data collection tool. The population in this research is some new students which amounted to 54 people. Data obtained through questionnaires that tested the validity and reliability using the product moment correlation formula and cronbach's alpha. Data analysis using multiple irregression analyst, F test, t test, coefficient of determination, dominant test and accompanied by testing classical assumption. The results showed that: (Image PT, Parents, peers and personality Individuals / interests) simultaneously influence the significance of the selection of university management program PGRI madiun. Factors Parentsless influence the selection of university management program PGRI madiun university. Citra PT, peers and personality Individuals / ask positive effect on the selection of university management program PGRI madiun. Citra PT has a dominant influence on the selection of university management program PGRI madiun university Keywords: Citra PT, parents of peers, personality Individuals / interests and management